Quality system study on St. Paul's Printing Press - Dela Paz, Rupher C.; Estrada, Eric D.C.; Remata, Eugene N. (Diliman, Quezon City College of Engineering, 1999)
The Society of St. Paul aims to achieve the spread of the Word of God through the Mass Media particularly in the publishing/printing business. St. Paul's Printing Press prints Homelife, Youngster, Sambuhay the New American Bible and other religious books as regular (weekly, and or monthly) publications. The group have chosen The New American bible as focus for the Quality System Study because the bible has the highest demand and sales in the market. The following are the results of the study: 1. Based on the FMEA, the printing process (chromoset) requires corrective action. 2. Using Ishikawa Diagram and Pareto Chart, all potential causes of problem such as blotted prints, defective paper, inadequate supply, wrong plating, power interruption, lack of training, wrong guide, inadequate water supply and inadequate supervision are identified and analyzed. 3. Printing process of bible on Week 1 was in control while on week 2 was out of control as can be seen at the control chart. To revised the control chart on week 2, sample number 4 is deleted since the assignable cause can be attributed to it. 4. The printing cost per good print produced in the present system is PhP 5.43. Based on the results of the study, the group have recommended the following: a. Replacement policy, using Dynamic Programming, in order to minimize the defective prints as will as to decrease operating cost and optimize resale value. b. Preventive Maintenance Program to increase productivity and decrease machine breakdowns. c. Installation of SPC and process adjustment at proportion nonconforming level, p=0.01 to decrease the number of defective prints. The installation of SPC will result a 2.95% reduction in manufacturing cost and an increase of 1.7% of conforming prints.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: St. Paul's Printing Press; Printing industry; Quality control